2017
DOI: 10.5812/aapm.14300
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Pendant Position and Traditional Sitting Position for Successful Spinal Puncture in Spinal Anesthesia for Cesarean Section

Abstract: BackgroundSuccess of spinal anesthesia in pregnant females is strongly influenced by the position of the patient at the time of spinal insertion. Pendant position is a new position introduced to increase the intervertebral spaces. The current study aimed at comparing successful spinal puncture among the patients with pendant position in comparison with the ones with traditional sitting position for the elective caesarean section.MethodsThe current study was a non-blinded, randomized controlled trial (RCT) (reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
1
11
1
1
Order By: Relevance
“…This phenomenon indicated the general anaesthesia used at each LP resveratrol administration may affect rat health and shorten their life span. In clinical practice, local anaesthesia is used for lumbar puncture [ 33 ]. Therefore, the adverse effects of repeated general anaesthesia on rat health do not apply to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon indicated the general anaesthesia used at each LP resveratrol administration may affect rat health and shorten their life span. In clinical practice, local anaesthesia is used for lumbar puncture [ 33 ]. Therefore, the adverse effects of repeated general anaesthesia on rat health do not apply to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pryambodho et al (14) compared spinal needle placement success rates between the pendant position and the TSP in 2014, and they found that the pendant position had a higher success rate of spinal needle placement. Pendant position is a sitting position with the patient’s underarms propped up by a cantilever.…”
Section: Discussionmentioning
confidence: 99%
“…The spinal anesthesia operator then has direct access to the median area of the vertebrae without being restricted by the upper part of the bed. This position is the most commonly used variant of the sitting position (12-14). The problem with this position is the need for a chair to prop up the patient’s feet and the need for two assistants to help move the patient’s feet to a supine position.…”
Section: Introductionmentioning
confidence: 99%
“…Poor positioning can result into multiple needle pricks and needle-to-bone contacts, thus increasing risk of backache, epidural hematoma, neural trauma and post-dural puncture headache (PDPH). [5][6][7][8] Lumbar spine curvature increases significantly in the last trimester of pregnancy, shifting center of gravity towards abdomen causing lumbar hyperlordosis. 9 Hyperlordosis produces vertebral space narrowing; while lumbar flexion is difficult to achieve in pregnant patients making median approach for spinal puncture very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…9 Hyperlordosis produces vertebral space narrowing; while lumbar flexion is difficult to achieve in pregnant patients making median approach for spinal puncture very difficult. 8 Sitting position has several modifications, i.e. traditional sitting position (TSP), pendant position, squatting position (SP), hamstring stretch position (HSP) and crossed-leg sitting position (CLSP).…”
Section: Introductionmentioning
confidence: 99%